Middle turbinate lateralization: A simple treatment for rhinologic headache - Somyos Kunachak (2018)
Objective: To introduce a minimally invasive method to eliminate the symptoms of contact-point rhinologic cephalgia. Study Design: A prospective study of 55 patients with chronic nasal or glabellar pain and endoscopically proven nasal origin. Methods: All 55 patients in whom endoscopic examination demonstrated a contact point between the middle turbinate and the nasal septum were treated by fracturing the middle turbinate lateralward using a small metal tongue depressor under 10% lidocaine HCL topical anesthesia. Results: Of the treated cohort, 48 (87%) of the patients had complete clinical symptom resolution after one treatment and all had resolution after two treatments. Recurrence occurred in 1 patient. There were no short-term or long-term adverse sequelae. The results persisted at a mean follow-up time of 50 months (range, 6-84 mo). Conclusion: Middle turbinate lateralization is safe and effective in eliminating the symptoms of rhinologic cephalgia induced by contact point between the middle turbinate and nasal septum.